The Difference in Job-seeking Stress between Perceived Parents’ Parenting Style and Perfectionism of University Students (Faculty of Teacher Training and Education, Universitas Terbuka, 2019)
The university students have several developmental tasks such as getting an academic goal, getting a job and preparing independence from their parents. But in Korea, those are not easy for university students. Especially, after the economic crisis in 1998, it became harder to find the right job of young people. To be independent of parents economically and psychologically was not easy . So, the purpose of this study is to investigate how university students feel job seeking stress as effects of perfectionism and perceive parenting style to help them effectively preparing as to be employed. The research questions were set up as follow: First, is there a difference in the university students' job-seeking stress according to perceived parenting style? Second, is there a difference in the university students' job-seeking stress according to perfectionism? To gain answers about these questions, a survey targeting the graduate students in Busan, South Korea was made. Five hundred survey questionnaires were distributed, and 423 responses were collected. The data were analyzed by t-test with SPSS 18. Results of this study were as follow. First, the lower-level care group experienced higher job seeking stress, personality stress, family stress and expectation stress than the other. And, the higher level of overprotection group suffered from higher job seeking stress and all of subtypes stress. Second, the higher level of self-oriented perfectionism students experienced more school stress than the lower one. Other-oriented perfectionism students experienced more job seeking stress, personality stress, and academic stress. And social imposed perfectionism group was suffering from all of subtypes stress. Limitations and suggestions for future study were provided.